2001
DOI: 10.1080/10587250108024010
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Chirality Due to Twisted Conformation in a Bent-Shaped Liquid Crystal Studied by Polarized Ft-Ir Spectroscopy

Abstract: Microscopic polarized fourier-transform infrared (FT-IR) measurements were performed in the antiferroelectric B2 phase of a bent-shaped liquid crystal molecule. In homogeneously chiral domains, the absorbance maximum appeared when the transmission axis of a polarizer was parallel to the layer normal for the phenyl ring stretching and C-0-C asymmetric stretching and that for the C=O stretching was almost perpendicular to that for C-0-C in the absence of a field. When a dc field was applied, the maximum for C-0-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 30 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…The conformational chirality was first proposed on the basis of the 13 C NMR data, in which the NMR signal due to the carbonyl carbons appears as a doublet for both the B2 and B4 phases . FT-IR measurements also supported the existence of the chiral conformation. , In our previous studies, however, we have not been concerned with the heterogeneity of the structures of the B2 phase. Additionally, the resolution of the NMR spectrometer and the temperature control facilities were not sufficient to obtain qualitative data, especially in the high-temperature B2 phase.…”
Section: Introductionmentioning
confidence: 71%
“…The conformational chirality was first proposed on the basis of the 13 C NMR data, in which the NMR signal due to the carbonyl carbons appears as a doublet for both the B2 and B4 phases . FT-IR measurements also supported the existence of the chiral conformation. , In our previous studies, however, we have not been concerned with the heterogeneity of the structures of the B2 phase. Additionally, the resolution of the NMR spectrometer and the temperature control facilities were not sufficient to obtain qualitative data, especially in the high-temperature B2 phase.…”
Section: Introductionmentioning
confidence: 71%
“…In fact, the bias rotational direction of the carbonyl carbons on the ester linkages between the central core and two side wings can make such a twist conformation . NMR , and IR data , also strongly support this assumption. This bias twisting of the carbonyl groups was also detected by time-resolved FTIR technique by Shilov et al In a recent study, Jakli et al have observed optically active domains with clear boundary in both anti-ferroelectric and ferroelectric transformed states in an all ester banana-shaped molecules.…”
Section: Discussionmentioning
confidence: 87%
“…One is that the carbonyl groups are relatively parallel to the layer and the other is perpendicular. Takezoe and co-workers have proven this specific molecular orientation in the B2 phase of the P-n-O-PIMB homologues by using FT-IR spectroscopy, , and they have found that such a molecule tilts in the layers with the carbonyl groups relatively parallel to the layer interface as shown in Figure d. The change of the molecular conformation by rotating of the carbonyl groups should be inevitably followed by the alternation of the tilt direction in the layer, which is supposed to have a high energy barrier.…”
Section: Discussionmentioning
confidence: 91%
“…The molecular conformational chirality in achiral bent‐core molecules has been theoretically predicted by the Monte Carlo simulations and density functional theory (DFT) . The existence of such molecular conformational chirality in achiral bent‐core molecules has been also verified by vibrational CD, nuclear magnetic resonance (NMR), and Fourier‐transform infrared (FTIR) absorption spectroscopy . It should be noted that Schenning et al reported the spontaneous symmetry breaking in nanoporous polymer particles of hydrogen bonded smectic liquid crystalline monomers, where equal quantities of enantiomeric single‐domain droplets with either positive or negative tilt of the molecular orientation within the concentric layers were observed.…”
Section: Chirality In Thermotropic Liquid Crystalsmentioning
confidence: 95%